An Integrated Maritime Fusion Governance Model: An AHP-Based Escalation Framework for Maritime Security (Journal Keamanan dan Keselamatan Maritim, 2026)
Maritime security governance in archipelagic states such as Indonesia suffers from fragmented institutions, overlapping mandates, and the absence of structured escalation logic linking threat conditions to response levels. This study addresses these gaps by proposing and demonstrating the Integrated Maritime Fusion‑Governance Model (IMFGM), a decision framework that combines fusion centre operations, escalation protocols, and quantitative multi‑criteria analysis. Using a simulated Analytical Hierarchy Process (AHP) grounded in theoretical escalation theory and maritime operational doctrine, the model evaluates four Siaga alert states (Siaga 4 normal monitoring to Siaga 1 maximum readiness) across three primary criteria (strategic, operational, tactical) and six sub‑criteria (indicators, threat trends, Common Operational Picture, coordination, intercept control, target accuracy). The results reveal that tactical utility dominates (weight = 0.63), with intercept control accounting for nearly half of the global decision priority (0.473). Under baseline assumptions, Siaga 1 ranks highest (0.46), followed by Siaga 2 (0.31), Siaga 3 (0.15), and Siaga 4 (0.08). Sensitivity analysis confirms model adaptiveness: reducing tactical weight to 0.40 makes Siaga 2 optimal, while elevating strategic weight raises Siaga 3. The study extends Bueger’s maritime security assemblage framework by adding decision and escalation dimensions. Policy recommendations include establishing a national fusion centre with prioritised data hierarchies, formalising quantified escalation protocols, strengthening civil‑military coordination through joint standard operating procedures, enhancing C4ISR interoperability, and conducting empirical AHP surveys for model calibration. Limitations include the use of simulated rather than empirical expert judgments and the static nature of the AHP framework. The IMFGM provides a transparent, replicable architecture for maritime escalation governance pending real‑world validation.